Buku Resep 20 Hidangan Olahan Kacang Tanah Khas Indonesia - Widarson, Nella Nevila; Indra, Febryola; Patricia, Sharen; Wijaya, Halim Adi (Gastronary, 2024)
This article discuss about a recipe book containing 20 recipes using beans of Indonesia "Variation of Signature Indonesian Peanut Preparation" that introducing types of dishes that use beans in Indonesian culinary, helping readers to broaden horizon about types of beans products and dishes, also helping readers to cook various dishes containing beans that are simple, practical, and easy to make daily to fulfill daily nutritional intake. This research is using qualitative approach with secondary data obtained from literature review, internet website, and hedonic test with experts that relate to Indonesian bean dishes. The 20 recipes of Indonesian bean dishes then are selected to be tested on expert panelist, which is a chef or a cook that is skilled an experienced in food production or cuisine, especially Indonesian. The test is conducted using hedonic and questionnaire analysis. The research result shows that this recipe book contains interesting and easy to understand recipes, also obtaining above five in average in questionnaire analysis and hedonic test. This recipe book is acknowledged to have potential in empowering Indonesian bean dishes. The writer however, still realizes the downside of the recipe book and write several suggestions, such as providing complete information on the description of dishes, using simple language that is easy to understand, also include more photos and illustration, and recipe making steps.